2007
DOI: 10.1016/j.juro.2006.11.061
|View full text |Cite
|
Sign up to set email alerts
|

The Male Perineal Sling: Assessment and Prediction of Outcome

Abstract: The male perineal sling can be an effective surgical treatment for stress incontinence in the appropriate patient. The procedure is most successful in patients with lesser objective degrees of incontinence. The Patient Global Impression of Improvement is an effective tool for assessing outcome for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 19 publications
7
54
1
2
Order By: Relevance
“…Only the severe incontinent subgroup (24h pad test >400g) showed significantly less displacement of the anterior bladder neck than the continent group during contraction (p=0.022). These ultrasound findings are consistent with the literature and may explain the surgical results of the study by Fischer, et al (15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only the severe incontinent subgroup (24h pad test >400g) showed significantly less displacement of the anterior bladder neck than the continent group during contraction (p=0.022). These ultrasound findings are consistent with the literature and may explain the surgical results of the study by Fischer, et al (15).…”
Section: Discussionsupporting
confidence: 92%
“…However, several studies have shown that patients with severe incontinence did not obtain results as satisfactory as those patients with mild to moderate incontinence (21-23). Fischer et al observed in 62 patients, those who had a 24h pad test <423g showed a success rate six times higher than those who had a test >423g (15).…”
Section: Discussionmentioning
confidence: 95%
“…The sling is increasingly being applied. The known effects are primarily short term: 40-90% need one or fewer pads per day and 16-76% require no incontinence material after an average of 12-18 months [10][11][12] . Bulking agents have shown reasonable short-term results.…”
Section: Introductionmentioning
confidence: 99%
“…Published success rates range from 38 to 76% depending on the outcome measures used. The most common complications are infection and temporary urinary retention [17,18,19]. Less common complications include persistent urinary retention (3% rate) and erosion of the sling into the urinary tract (2% rate) [18].…”
Section: Discussionmentioning
confidence: 99%